Frequency analysis of the ACTN3 gene polymorphism in children with isolated or combined orthodontic pathology with allergic rhinitis - T. Ye. Shumna; O. V. Voznyi; T. P. Zinchenko; O. M. Kamyshnyi (Kazimierz Wielki University, 2020)
Purpose. Determination and frequency analysis of the ACTN3 gene (actinin, alpha 3) rs1815739 polymorphism, responsible for metabolism, strength and speed of muscle movement, including the maxillofacial apparatus, in children with distal occlusion and allergic rhinitis. Materials and Methods. To study the ACTN3 gene (rs1815739) polymorphism, the molecular and genetic study was conducted in 100 children aged 6 to 18 years. The 26 patients with distal bite and allergic rhinitis were included in the first study group; the second group consisted of 23 children with a distal bite; the third group included 30 children with allergic rhinitis and the fourth group was made up of 21 almost healthy children. All children did not have a statistically significant difference in sex and age. The molecular and genetic study was carried out in the Department of Molecular and Genetic Research of theTrainingMedicalLaboratoryCenter in the Department of Microbiology of theZaporizhiaStateMedicalUniversity, Zaporizhia. The obtained study results were analyzed using non-parametric methods of statistical analysis of the licensed software package «Statistica 6.1. RU». The population genetic analysis with the distribution of alleles and genotypes of the ACTN3 gene frequency is presented in accordance with the Hardy-Weinberg principle. Results. Studying the distribution of allelic genes and genotypes of the ACN3 polymorphism (actinin, alpha 3) rs1815739 showed that among all examined children, the alpha actinin-3 protein was synthesized sufficiently in 36% of children with the homozygous C / C genotype, while in case of European population it was equal to 31%; and insufficiently - in 11% of those examined with the homozygous T / T genotype (in the European population - in 17.9%); in a smaller amount - in 53% of children with the heterozygous C / T genotype, which frequency corresponded to the European population (51.1%). The genotypes had the following distribution in the study groups: in children with a combination of allergic and orthodontic pathology; with distal bite; with allergic rhinitis and in healthy children, respectively: homozygous C / C genotype - 38.46%; 56.52%; 33.33%; 14.3%; homozygous T / T genotype - 11.5%; 8.7%; 6.67%; 19.05%; heterozygous C / T genotype - 50%; 34.78%; 60%; 66.67%. In children with distal bite, the homozygous C / C genotype (rs1815739) of the gene coding alpha-actinin-3 protein synthesis was associated with the odds ratio OR = 7.80, CI [1.79 - 34.07], while in children with heterozygous genotype C / T the odds of being healthy was OR = 3.75, СІ [1.08 - 13.07]. Conclusions. The dominant observation of the C / C genotype (rs1815739) of the gene coding alpha-actinin-3 protein synthesis in children with distal bite may indicate the role of muscle strength and their pressure on the dentition in the process of formation of children tooth-maxillary anomalies, which shall be taken into account when selecting individual treatment-and-preventive myogymnastics and apparatus treatment for such patients.